SURVEI KESEHATAN HIDUNG MASYARAKAT DI DESA TINOOR 2 - Ishak, Windy S.; Pelealu, Olivia; Tumbel, R. E. C. (e-CliniC, 2015)
Abstract: Physiologically, a nose has several functions, for instance as a filter that enables it to be the first-line defense and serves an important function for protecting the body against the disadvantageous condition from our surroundings. The main purpose of this research is to describe about how the health survey of nose on the locals in Tinoor 2 is. The method used on this research is descriptive survey with cross sectional approach. The subject of this research is the locals of Tinoor 2 who willingly participated in. The total of participants is 40 divided into 13 females and 27 males. Findings show that 62,5% and 60% are the result of normal right and left nasal cavity examination. Meanwhile, 32,5% and 35% are for the broad right and left kavum nasi examination, also both of the medium and narrow are 5%. 70% and 67,5% are the result of normal right and left concha examination, 15% and 17,5% are both for edema examination, hyperemia on both sides are 2,5%. 92,5% and 90% are the result of normal right and left mucous examination, while hyperemia with 7,5% and 10%. 97,5% is the result of normal right and left secretion examination, and serous on both sides are 2,5%. 82,5% is the result of normal right and left septum examination, and nasal septum deviation on both sides are 17,5%. There’s none post nasal drip within the examination. Conclusion: Of all examination that has been accomplished, most of them result to Normal.Keywords: health survey, physical examination of noseAbstrak: Hidung secara fisiologis mempunyai beberapa fungsi seperti sebagai penyaring dan pertahanan lini pertama dan pelindung tubuh terpenting terhadap kondisi lingkungan yang tidak menguntungkan. Tujuan penelitian untuk mengetahui bagaimana gambaran survei kesehatan hidung masyarakat desa Tinoor 2. Desain penelitian yang digunakan adalah deskriptif survei dengan pendekatan cross sectional. Subjek penelitian masyarakat desa Tinoor 2 yang bersedia mengikuti penelitian. Responden 40 orang, dengan jumlah laki-laki dan perempuan 13 dan 27 orang. Pemeriksaan kavum nasi kanan kiri normal 62,5% dan 60%, pada pemeriksaan kavum nasi kanan kiri lapang 32,5% dan 35%, sedang sempit keduanya 5%. Pemeriksaan konka kanan kiri normal 70% dan 67,5%, udim yaitu 15% dan 17,5%, hiperemis dikeduanya 7,5%, pucat dikeduanya 5%, konka dengan udim dan hiperemis keduanya 2,5%. Pemeriksaan mukosa kanan kiri normal 92,5% dan 90%, hiperemis 7,5% dan 10%. Pemeriksaan sekret kanan kiri normal keduanya 97,5%, serus keduanya 2,5%. Pemeriksaan septum kanan kiri normal keduanya 82,5%, deviasi dikeduanya 17,5%. Post nasal drip tidak ditemukan. Simpulan: Dari pemeriksaan hidung yang dilakukan pada responden, ditemukan hasil terbanyak adalah normal.Kata kunci: survei kesehatan, pemeriksaan fisik hidung